2013
DOI: 10.21608/jacb.2013.53230
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF OLIVE LEAF EXTRACTS (OLEs) AS ANTIOXIDANTS ON THE BIOCHEMICAL CHANGES IN CANOLA OIL DURING HEATING

Abstract: The present study was undertaken to evaluate and compare the potential of antioxidant activities of olive leaf extracts(OLEs) with other natural or synthetic antioxidants. So, the aim of this study was to assess the effectiveness of methanolic-,ethanolic-,and water-olive leave extracts (OLEs) and compare it with other antioxidants such as green tea extract , tert-butylhydroxyquinone (TBHQ) , citric acid on the oxidative stability of virgin canola oil during storage at an oven at 63±1°C temperature for 0,5,10,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…Free green tea extracts at a concentration of 600 mg L −1 and liposomal extract at concentrations of 200, 600, and 1000 mg L −1 showed higher efficiencies, compared to BHT. These reports were similar to reports from other studies (Semwal & Arya, 2001;Hassan et al, 2013), in which, TBA values increased in sunflower and canola oils during storage.…”
Section: Thiobarbituric Acidsupporting
confidence: 92%
See 1 more Smart Citation
“…Free green tea extracts at a concentration of 600 mg L −1 and liposomal extract at concentrations of 200, 600, and 1000 mg L −1 showed higher efficiencies, compared to BHT. These reports were similar to reports from other studies (Semwal & Arya, 2001;Hassan et al, 2013), in which, TBA values increased in sunflower and canola oils during storage.…”
Section: Thiobarbituric Acidsupporting
confidence: 92%
“…Chen et al (1996) studied antioxidant effects of ethanolic extracts of green, white, yellow, black, dark-green, and oolong teas on heated canola oil at 100 C. Results showed that the green, white, and yellow extracts showed higher antioxidant activities than BHT to inhibit oxidation of canola oil. Hassan et al (2013) used olive leaf ethanolic, methanolic, and water extracts as natural antioxidants in canola oil. The lowest peroxide value belonged to the ethanolic extract followed by methanolic and water extracts.…”
Section: Peroxide Valuementioning
confidence: 99%
“…Free green tea extract at concentration of 600 mg/L and liposomal extract at 200, 600 and 1000 mg/L showed higher efficiency in compare to BHT. The obtained results are in agreement with other reports (Semwal & Arya., 2001;Hassan et al, 2013). They found TBA values, respectively, on the sunflower and canola oils, increased during storage time.…”
Section: Thiobarbituric Acid Reactive Substances (Tbars)mentioning
confidence: 95%
“…Hassan et al used of olive leaf ethanolic, methanolic and water extract as natural antioxidant on the canola oil. The lowest peroxide value related to ethanolic extracts followed by methanolic and water extracts (Hassan et al, 2013). Koketsu and Satoh compared antioxidant effects of green tea polyphenols at 40 and 60 mg/L and tocopherol in the 200 mg/L concentration on the soybean oil.…”
Section: Peroxide Valuementioning
confidence: 99%